Análisis de fuentes nitrogenadas en los pastos Brachiaria en el cantón Babahoyo - Gaibor Litardo, Jamil Ramiro (2020)
Brachiaria is a grass that contains about 100 species distributed throughout the tropics, generally used for the production of pasture. In Ecuador this genus has become of great economic importance due to its establishment in degraded areas, being very used by the cattle producers of the Ecuadorian coast, including the producers of the Babahoyo canton. The objective of the present final work corresponding to the practical component of the Complexivo examination was carried out with the purpose of analyzing the nitrogenous sources used in the Brachiaria grasses in the Babahoyo canton, where the importance of nitrogen for the production of biomass in this genus was highlighted, increasing its parameters of dry matter, green matter and productive efficiency using nitrogenous sources in the different species of production within the area such as B. humidicola, B. arrecta and B. brizhanta, highlighting the Urea which generates better results. Opposite to the efficiency of nitrogen, the problem is the poor preparation of the cattle producers due to the inadequate or null fertilization practices, generally because they do not start working the pastures as a crop, causing production losses and decreasing its nutritional value, recommending to carry out in the pastures all the adequate agronomic managements that improve their cattle production process. It has been demonstrated that the use of nitrogen in correct doses increases the forage production of this grass, generating positive effects and encouraging producers to use this macro-element that reduces their production costs and increases the nutritional quality of the cattle feed.